Perancangan Sistem Informasi Pengelolaan Persediaan untuk Memperbaiki Proses Bisnis dengan Menggunakan Metode Business Process Improvement dan Waterfall: Studi Kasus UD Dwi Mulya Plastik - Aulia, Syifa Bilatifa; Ardiansyah, Muhammad Nashir; Muttaqin, Prafajar Suksessano (IAI Nasional Laa Roiba Bogor, 2024)
UD Dwi Mulya Plastik is an upper-middle class MSME that produces various kinds of plastic-based household furniture. During the last year, namely 2023, in the application of existing business processes there was a mismatch between inventory in actual conditions and company records. This is because UD Dwi Mulya Plastik does not yet have a system that helps in the process of recording incoming materials, outgoing materials, and for monitoring material inventory stocks. The recording process is still done manually, namely with a notebook. Therefore, in the recording process errors often occur so that the amount recorded does not match the actual amount of material in the warehouse. In addition, the absence of a system that can help the process of monitoring inventory movements is also another cause of inventory data mismatches. With this, the author conducted research to help solve the problem, namely by designing a proposed business process improvement by designing a website-based information system that can be used as a tool in the process of recording incoming materials, outgoing materials, and also monitoring material stock. The process of designing the proposed business process is by using the Business Process Improvement (BPI) method and designing information systems using the Waterfall method. With the results of the proposed business process design and information system, it can help companies in managing inventory that is more structured and can reduce information or data errors. By implementing the proposed business process, the company can eliminate unnecessary activities in the existing business process and can make changes to activities that are considered inefficient, namely material inventory management. In addition, in the application of the proposed business process there is a reduction in cycle time of 18.37 minutes. Suggestions for further research are that future researchers are expected to strengthen the security aspect of the system and also the company can do web hosting so that users can access the website anytime and anywhere.